PENGARUH PEMBERIAN JUS ALPUKAT TERHADAP PENURUNAN TINGKAT NYERI HAID (DISMENOREA) PADA SISWI KELAS VII DI SMPN 9 KOTA MADIUN - Wahyuning, Binar; Purnama Atmadja, Bayu; Yuliana, Fitria; Fika, Yudha (Universitas Cokroaminoto Palopo, 2024)
Dysmenorrhea is pain or soreness in the lower abdomen that occurs when women experience the menstrual cycle. Risk factors associated with the incidence of dysmenorrhea are age, menstrual cycle, and readiness to face menstruation. Non-pharmacological therapy to reduce menstrual pain (dysmenorrhea) is one of them by consuming Avocado Juice which contains (Calcium, Magnesium, Vitamin B6, and Vitamin E) which can reduce dysmenorrhea. The purpose of this study was to determine the effect of Avocado Juice on reducing the level of menstrual pain (Dysmenorrhea) in seventh grade students of SMPN 9 Madiun City. Research with Pre-experimental methods using the One Group Pre-Post Test Design approach. The sampling technique used purposive sampling with a sample of 30 respondents. The menstrual pain scale before being given Avocado Juice is 6,70 with the most scale is 6 and the highest pain scale level is 9, and the menstrual pain scale after being given Avocado Juice is 3,37 with the most scale is 3 and the highest pain scale level is 6. The results of the Wilcoxon Test analysis of giving Avocado Juice for 2 days obtained a p-value of 0.000 <0.05, then it shows that there is an effect of giving Avocado Juice to class VII students at SMPN 9 Madiun City. Based on the results of the analysis of avocado juice administration on reducing the level of menstrual pain (dysmenorrhea) in seventh grade students at SMPN 9 Madiun City. It is hoped that for respondents Avocado juice can be used as a material consideration in an effort to overcome menstrual pain (dysmenorrhea) non-pharmacologically.